"Like Walking in a Fog"—Parents' perceptions of sleep and consequences of sleep loss when staying overnight with their child in hospital. (13th November 2019) - Angelhoff, Charlotte; Sjølie, Hege; Mörelius, Evalotte; Løyland, Borghild
Summary: Disruption of parental sleep in hospital, with frequent awakenings and poor sleep quality, limits the parents' resources to meet the child's needs and maintain parental wellbeing. The aim of the study was to explore and describe how parents perceive their sleep when staying overnight with their sick child in hospital. A further aim was to explore and describe parents' perception of what circumstances influence their sleep in the hospital. Twenty‐two parents who were accommodated with their sick child (0–17 years) in paediatric wards in Norway and Sweden participated. Interviews were conducted during the hospital stay to elicit their perspectives. Phenomenography was used to analyse data. Two descriptive categories were found: (a) "Perceptions of sleep", with two sub‐categories: "Sleep in the paediatric ward" and "Consequences of sleep loss"; and (b) "Circumstances influencing sleep in the paediatric ward" with three sub‐categories: "The importance of the family", "Information and routines at the paediatric ward", and "Accommodation facilities". Parents' sleep and needs must be acknowledged in paediatric wards. An individual plan of care for the upcoming night could be a valuable tool for both the parents and nurses. The child's medical needs must be met with respect to the parents' willingness to take part in the child's care during the night, and the need for rest and sleep for both parent and child.